2011
DOI: 10.5551/jat.6379
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin is Associated with Serum High Molecular Weight Adiponectin in Japanese Community-Dwelling Persons

Abstract: Aim: Serum high molecular weight (HMW) adiponectin improves insulin sensitivity, and a decreased level of serum HMW adiponectin has been reported as a risk factor for the development of diabetes and coronary heart disease. This association may be further confounded by the hemoglobin status, which is involved in the development of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…Our findings confirm previous investigations reporting that circulating adiponectin is inversely related with adiposity and glucose, and directly related with HDL cholesterol (Belalcazar et al 2012; Cnop et al 2003), however endothelial cell adiponectin is not related with these factors in our study. Our data also confirm that higher circulating adiponectin levels are associated with lower red blood cell count, hematocrit and hemoglobin concentration (Aso et al 2009; Aso et al 2012; Kawamoto et al 2011). Surprisingly, in our study higher endothelial cell adiponectin levels are associated with higher levels of these factors, but the underlying mechanisms are unknown.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings confirm previous investigations reporting that circulating adiponectin is inversely related with adiposity and glucose, and directly related with HDL cholesterol (Belalcazar et al 2012; Cnop et al 2003), however endothelial cell adiponectin is not related with these factors in our study. Our data also confirm that higher circulating adiponectin levels are associated with lower red blood cell count, hematocrit and hemoglobin concentration (Aso et al 2009; Aso et al 2012; Kawamoto et al 2011). Surprisingly, in our study higher endothelial cell adiponectin levels are associated with higher levels of these factors, but the underlying mechanisms are unknown.…”
Section: Discussionsupporting
confidence: 84%
“…There are also reports of an inverse relation of circulating adiponectin with adiposity and glucose, and a direct relation with HDL cholesterol (Belalcazar et al 2012; Cnop et al 2003). Interestingly, higher circulating adiponectin has also been linked with decreased renal function (Kawamoto et al 2010; Kruger et al 2011) and markers of anemia (red blood cell count, hematocrit, and hemoglobin) (Aso et al 2009; Aso et al 2012; Kawamoto et al 2011). However, it is not known whether endothelial cell adiponectin is similarly related with these factors and with circulating adiponectin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Several new studies show that increased serum γGT levels are associated with higher hemoglobin levels [4], hyperuricemia [5], metabolic syndrome, oxidative stress [6], higher fasting glucose levels [7,8], resistance to insulin [9], changes in levels of serum cholesterol, lowdensity lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglycerides [10], and cardiovascular diseases [11]. Serum γGT measurement is also known as a marker of diabetic nephropathy [12].…”
Section: Introductionmentioning
confidence: 98%
“…12 Participants were recruited at the time of their annual health examination in a rural town with a total population of 11,136 (as of April, 2002) and located in Ehime prefecture, Japan, in 2002. Among the 9,133 adults (4,395 male) aged 19-90 years in this population, 3,164 (34.6%) subjects participated in this study through a communitybased annual medical check-up process.…”
Section: Subjectsmentioning
confidence: 99%
“…10 It is also associated with the development of chronic heart failure, 11 CVD, and CVD mortality. 10,11 In addition, Kawamoto et al 12 reported that GGT showed a significant correlation with each HMW adiponectin and metabolic syndrome, suggesting a possible interaction between these two key markers. However, there are few reports on the relationship between GGT, HMW adiponectin, and metabolic syndrome in Japan.…”
Section: Introductionmentioning
confidence: 97%